A binary solvent mixture-induced aggregation of a carbazole dendrimer host toward enhancing the performance of solution-processed blue electrophosphorescent devices1. Issue 19 (21st May 2015) - Liu, Lihui; Liu, Xuejing; Zhang, Baohua; Ding, Junqiao; Xie, Zhiyuan; Wang, Lixiang
<x xml:space="preserve">Abstract</x> The trade-off between charge transport and energy transfer is realized by manipulating the dendrimer host H2 aggregation with binary solvent mixture, along with 25% device efficiency enhancement for FIrpic based blue PhOLED.